Foot Skin Ischemic Necrosis following Heel Prick in a Newborn. (28th October 2013) - Koklu, Esad; Ariguloglu, Erdal Avni; Koklu, Selmin
Abstract : There are only a few reports on side effects after heel prick in neonates although heel prick has been performed all over the world for many years. The medicine staff had obtained only a drop of blood by pricking the baby's heel using a lancet without compressing the heel or foot to measure his blood glucose level 3 hours after birth. However he developed a severe and hemorrhagic skin reaction on his entire left foot, beginning 30 minutes after obtaining the drop of blood by pricking the baby's heel using a lancet. The lesion, which was treated with topical mupirocin and povidone-iodine solution daily, slowly decreased in size and had almost fully resolved within 3 weeks. He was healthy and 9 months old at the time of writing this paper. We herein report a case of foot skin ischemic necrosis following heel prick in a newborn. To our knowledge this patient is the first case of foot skin ischemic necrosis due to heel prick in newborns.